Implementation of a Singular Value Decomposition Module on an FPGA - Hosseinimehr, Masoud; Montealegre, Norma (The 23rd IASTED International Conference on Parallel and Distributed Computing and Systems (PDCS 2011))

Automatic Feature Classification for Object Detection based on Motion Analysis - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 5th International Conference on Automation, Robotics and Applications (ICARA))
In this paper an approach for automatic feature classification based on their motion in the image plane is introduced. By combining concepts of the human perception of motion with techniques belonging to the area of cluster analysis, we subsequently abstract the visual data in order to separate features, whose motion is caused by the sensor motion from features, which possibly belong to dynamic objects in the environment. The presented algorithm exclusively works on data, that can be extracted from the two dimensional image plane. Hence, no external data like the current motion of the applied camera is required. Furthermore, the algorithm works on any type of tracked feature, as long as it can be statistically represented. The results of the presented approach constitute a very good starting point for additional object detection mechanisms.

Towards Using Virtual Forces for Image Registration - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (The 5th International Conference on Automation, Robotics and Applications (ICARA 2011))
This paper introduces a novel method for registering a large amount of aerial images when camera parameters are almost unknown and no reference images are available. The envisioned application is the creation of an overview map of a disaster area from images made by unmanned aerial vehicles (UAVs) equipped with cameras. The camera systems only have uncertain information about flight attitude. With traditional methods, the relatively small perspective errors per image sum up over time resulting in perspective errors which prevent building a consistent map from successively arriving images. By using virtual forces between images, the image parameters are continuously adapted to the current map. The small projective errors of quasi orthographic images are distributed among overlapping images. Having UAVs which deliver quasi orthographic images, our approach can build a contemporary overview without the need to have all images in advance.

Determination of the Schmidt number - Sperling, Jan; Vogel, W. (Physical Review A)

The Schmidt number as a universal entanglement measure - Sperling, Jan; Vogel, W (Physica Scripta)

Zur Bewertung von Verlustgesellschaften nach den Änderungen des §8c KStG durch das Wachstumsbeschleunigungsgesetz - Diller, M.; Kundisch, Dennis; Späth, T. (CORPORATE FINANCE biz)

How to manage and Search/Retrieve Information Objects - Dannewitz, Christian; al, et (Architecture and Design for the Future Internet)

Integrating Generic Paths and NetInf - Dannewitz, Christian; al, et (Architecture and Design for the Future Internet)

A Distributed Multi-UAV Path Planning Approach for 3D Environments - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (The 5th International Conference on Automation, Robotics and Applications (ICARA 2011))
During rescue scenarios it is indispensable to obtain an overview of the situation. Unmanned aerial vehicles (UAVs) can gather the necessary information in a fast and efficient way. This paper presents an approach for path planning in 3D environments offering a solution to explore disaster areas including, e.g., partially or completely destroyed buildings. Using multiple UAVs decreases the time needed to receive a complete overview if the problem of coordination and task allocation is solved. We present an approach for the use of multiple UAVs. The UAVs work in a distributed manner without any central coordination instance and cover the exploration of terrains as well as goal-oriented path planning. When using multiple UAVs redundant exploration is avoided through the use of inter-UAV-communication. The approach is based on potential fields and uses the simplicity of the gradient method to calculate paths for fast exploration of the terrain.

A Bio-inspired Coverage and Connectivity Maintenance Algorithm - Mathews, Emi; Graf, Tobias; Kulathunga, K. S. S. B. (Sixth International ICST Conference on Bio-Inspired Models of Network, Information, and Computing Systems)

Aspect enhanced functional coverage driven verification in the SystemC HDVL - Kuznik, Christoph; Müller, Wolfgang (Proc. of the 8th International SoC Design Conference 2011 (ISOCC 2011))

IP-XACT based System Level Mutation Testing - Xie, Tao; Müller, Wolfgang (Proceedings of the 16th IEEE International High Level Design Validation and Test Workshop (HLDVT))

Model-driven runtime resource predictions for advanced mechatronic systems with dynamic data structures - Henkler, Stefan; Oberthür, Simon; Giese, Holger; Seibel, Andreas (International Journal of Computer Systems Science & Engineering 26 (6))

Enabling Constraint-based Binary Reconfiguration by Binary Analysis - Baldin, Daniel; Grösbrink, Stefan; Oberthür, Simon (International Journal on Computing (JoC) 1(4))

F-DRARE: A Framework for Deterministic runtime adaptation of Cyber Physical Systems - Bin Tariq, Fahad (1st International Workshop on Adaptive Services for the Future Internet, 4th European Conference, ServiceWave 2011)

High-Level Construction of Emergent Self-Organizing Behavior in Massively Distributed Embedded Systems - Orfanus, Dalimir; Janacik, Peter; Eliassen, Frank; Orten, Pal (Proceedings of Third World Congress on Nature and Biologically Inspired Computing (NaBIC2011))

Ausgewählte Probleme des Logistikmanagements

HDL-Mutation Based Simulation Data Generation by Propagation Guided Search - Xie, Tao; Müller, Wolfgang (Proceedings of the 14th Euromicro Conference on Digital System Design (DSD))

A Test Bed for Investigating Self-X Properties in Multi-Robot Societies - Jungmann, Alexander; Lutterbeck, Jan; Werdehausen, Benjamin; Kleinjohann, Bernd (Proceedings of the 9th IEEE International Conference on Industrial Informatics (INDIN))
In this paper, we introduce a test bed for demonstrating and investigating self-x properties, such as self-optimization and self-organization, within the scope of multi-robot societies under realistic conditions. By doing so, we shift the investigation and demonstration of biologically inspired mechanisms from the simulative point of view to a dynamic and more complex realistic environment. For this purpose, we developed a controlled real-world environment to overcome common problems such as self-localization. Furthermore, we elaborated a concept for a descriptive robotic real-world game. By means of this game, we provide an instrument, which is easily accessible for any kind of audience on the one hand, while it still leaves enough space for an extensive scientific investigation on the other hand.

Miniature Robot BeBot: Mechatronic Test Platform for Self-X Properties - Gausemeier, Jürgen; Schierbaum, Thomas; Dumitrescu, Roman; Herbrechtsmeier, Stefan; Jungmann, Alexander (Proceedings of the 9th IEEE International Conference on Industrial Informatics (INDIN))
Machines are omnipresent. They produce, they transport. Machines facilitate work and assist. The increasing penetration of mechanical engineering by information technology enables considerable benefits. We refer to such systems as advanced mechatronic systems, which relay on the close interaction of mechanics, electric/electronics, control engineering and software engineering. Hence, the design and production of such systems is an interdisciplinary and complex task. Our ambition is a new school for the design of advanced mechatronic systems. Consequently, we need an avant-garde basic system which can be used to develop and to test future applications. The miniature robot BeBot is such a basic system. This robot constitutes the test bench for the applications, being based on modern approaches, such as self-optimization, self-organization and self-coordination as well as on the use of new manufacturing technologies.